To the Issue of the Applicability of P. C. Schmitter`S Theory of Corporatism in Modern Russian Political Space - A. E. Kostin (Управленческое консультирование)
In this article, the author set the goal to determine in what measure the provisions of the classical theory of corporatism of Phillipe C. Schmitter can be applied in the characterization of the modern Russian model of corporate relations. The author focuses on the determination of the type of corporate model of representation of interests in the Russian political space, based on the characteristics of the state and social types, which was formulated by P. C. Schmitter. As a result, the author comes to the conclusion that the Russian model of corporatism is close to the state type of corporatism, but has specific properties that the author tries to formulate.